Architects of stability? - Kapstein, Ethan B. (Bank for Internat. Settlements, 2006)
The objective of this paper is to provide a balanced assessment of international cooperation among financial regulators, with a focus on banking supervision. While recognizing the undeniable – and even unexpected – achievements of these regulators in building a cooperative framework for financial supervision, we also suggest that this remains a work in progress, given the contemporary financial risk environment. Briefly, we argue that this environment – to the extent we understand it, for it remains opaque in important respects – has an almost paradoxical quality, in that risk has become both more consolidated and more atomized at the same time. On the one hand, large and complex financial institutions (LCFIs) which may be
Literaturverz. S. 19 - 20
Keywords: Arbeitspapier; Graue Literatur; Zentralbank; Internationale Zusammenarbeit; Bankenaufsicht; International cooperation